El enfoque estadial en el estudio del constitucionalismo latinoamericano: problemas y perspectivas. - Nikolai Nikolaevich, Marchuk (2013)
The author shows the limitations of traditionalmicroanalysis and two megaanalyticalapproaches –the formationaland civilizational– in the study of LatinAmerican constitutionalism. In exchange,he proposes estadial approach,whose strength is the ability to interpretthe past and present of constitutionalism,not only in Latin America, but on bothsides of the Atlantic Ocean, and also envisagechanges in the development of constitutionalismin the distant future.